Soya varieties show resistance to fungus - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Trials conducted by IITA in lbadan, Nigeria have shown that the grey fungus, Cercospora sojina, reduces yields of soya by as much as 65% in susceptible varieties. With the disease under control, soya could produce higher levels of protein for human...